Changing Families: A Preventive Intervention Perspective. Issue 3 (10th May 2019) - Cowan, Carolyn Pape; Cowan, Philip A.
Abstract : In this review of preventive interventions to promote healthy families, we begin with an account of how sociology and psychology have helped shape conflicting interpretations of changes in families over the past 70 years as evidence of either family decline or positive diversity. We argue that in either case, well‐validated programs are needed to strengthen families across the economic spectrum. Most parenting interventions have been designed for, and attended by, mothers. We present an empirically based family risk and protection model to provide a rationale for interventions that also include fathers and focus on the coparenting relationship. Using an example of 7 clinical trials of a couples group intervention for parents from diverse economic and social backgrounds, we show that including fathers and addressing the coparental relationship as well as parenting contributes to healthier outcomes for mothers, fathers, and children. Finally, we discuss implications for the future of family research and policy.